Thermodynamic case study of boundary layer viscous nanofluid flow via a riga surface by means of finite difference method - Shuguang Li; Yuchi Leng; Assmaa Abd-Elmonem; Kashif Ali; Nesreen Sirelkhtam Elmki Abdalla; Sohail Ahmad; Wasim Jamshed (Case Studies in Thermal Engineering, 2024)
The Riga plate is an electromagnetic actuator made out of permanent magnets and alternating electrodes on a flat surface. In the boundary layer flow across the Riga Plate, viscous dissipation is surveyed in this paper. The suitable boundary conditions have been assigned to the governing model for mass and heat convection phenomenon. A governing equation can be converted into non-dimensional form using similarity transformations. To create numerical solutions to physical phenomena, the finite difference approach can be utilized. Extensive graphical illustrations are provided for the effects of the buoyancy coefficient parameter, modified Hartmann number, parameter related to electrode and magnet width, Prandtl number, slip parameter, thermophoretic parameter, thermal radiation parameter, Schmidt number, chemical reaction rate parameter, suction parameter, Brownian motion parameter, volume fraction, Biot number, and Eckert parameter on velocity, temperature, and concentration distributions. By varying the Eckert number, the viscous dissipation effects can be obtained. Suction and slip parameters increase the velocity while decrease the temperature in both nanofluid cases. The high temperature and velocity of equally distributed nanofluids rise as the volume fraction increases. Thermal radiation promotes heat transport. The concentration of nanoparticles in the region around the plate increases as the chemical reaction parameter increases. The research findings are useful for thermal engineers and practitioners involved in the design and optimization of systems where boundary layer fluxes and heat transfer are important factors. Understanding the effects of viscous dissipation can lead to more reliable heat transfer estimates and more effective thermal management in real-world structures.